Length of Rainfall Season in Enugu, South East Nigeria (Global Journal of Human-Social Science, 2015)
The study length of Rainfall (RF) season in Enugu, South East, Nigeria from 1916 -2012 examines the trend in RF pattern over Enugu. Data for this work were extracted from the Nigerian Meteorological Agency (NIMET) Oshodi, Lagos archive for analysis. The results show that the date of Onset of RF over the years has extended or delayed slightly from 12 th March (71) day of the year in 1916 to about 15 in 2012. In analysing RF cessation, it was observed that RF cessation has reduced or shifted forward from 21st October to 10th October. The study further observed that the duration of RF over Enugu has reduced. The duration in 1916 was 256 days, in 2012 duration accounted for just 223 rainy days during the period, representing a decrease of about 30 days as shown by the trend line for RF duration. It was also discovered that the RF distribution of Enugu skewed positively an indication that total RF is reducing slowly. The RF season or duration over Enugu covers 7 months. This work discovered that, onset of RF has extended, while cessation date reduced, and duration of RF has also reduced pointing to high RF intensity, this can trigger flooding and soil erosion, therefore, the work suggests that every environmental related policies need to consult RF data and take account the benefits and demerits associated with it.
Keywords: climate change and fluctuation; rainfall parameters; wet and dry season; Enugu